The many branches of the tree; a personal view of Palaeobotany in Africa - Bamford, Marion (University of the Witwatersrand, Johannesburg, 2014)
Not available
Inaugural lecture presented at the University of the Witwatersrand, Johannesburg, 2014.
Keywords: Fossil woods; Palaeoclimate; Biostratigraphy; Dicroidium; Jurassic - Cretaceous wood; Cycads; Kirkwood-palaeofires project; Angiosperms; Orapa kimberlite pipe; African Cretaceous woods; Cretaceous Orapa flora; Miocene West coast woods; Vredendal Miocene; Arrisdrift Miocene; Cradle of humankind sites; Sterkfontein valley; Sterkfontein fossil woods; Wonderwerk Cave